Regulatory Emotional Self-Efficacy Buffers the Effect of Heart Rate Variability on Functional Capacity in Older Adults With Chronic Low Back Pain - Morais, Calia A.; DeMonte, Lucas C.; Bartley, Emily J. (Frontiers in Pain Research, 2022)
Introduction Chronic low back pain is one of the leading causes of disability globally among older adults. Prevailing research suggests that autonomic dysregulation places individuals at increased risk for chronic pain. This study examines the moderating role of emotional self-efficacy (ESE) on the relationship between heart rate variability (HRV) and pain related-outcomes, including movement-evoked pain (MEP) and physical functioning. Methods In a secondary analysis of the Adaptability and Resilience in Aging Adults (ARIAA) study, a total of 58 adults (aged 60 and older) with chronic low back pain (cLBP) completed the PROMIS self-efficacy for managing emotions questionnaire and the 6-minute walk test (6 MWT) to assess functional capacity and MEP. Heart rate variability, indexed by the frequency domain, was assessed for 5 min during rest. Results For pain-related outcomes, having a lower body mass index (p = 0.03) was associated with better functional capacity on the 6MWT, while higher education level (p = 0.01) and less pain duration (p = 0.00) were correlated with lower MEP. After controlling for sex, age, and body mass index, an increase in low-frequency HRV (LF-HRV) was associated with poorer physical functioning among individuals low in ESE (b = −0.12 p = 0.03). No significant moderation effects were observed for MEP. Conclusion Our results bring attention to the degree to which ESE influences the relationship between LF-HRV and physical functioning. Interventions that enhance adaptive psychological processes such as ESE may dampen ANS dysregulation and mitigate risk for adverse pain outcomes among older adults with cLBP.